Understanding Algebra - Taqwa Nur Ibad; Muhammad Ardy Zaini (Bidayatuna, 2019)
Today, many students are not familiar with algebra. They consider algebra to be a scary lesson. Not even a few who really hate this lesson. Starting from there, algebra material always tries to be presented in a more pleasing form. Appearances that feel new are indeed worth showing to increase the love of algebra. The concept of algebra, consciously or unconsciously, has actually been taught from an early age in kindergarten, Play Group. For example when studying while playing / singing accompanied by a knock on a table, chair or other object. By paying attention to the sequence of repeating beats, the teacher can simply explain the concept of algebra to the child according to his level of reasoning. One difficulty in solving problems is to explain the answers we try to find from the unknown. In algebra if they are numbers, they are often explained by letters such as 'a' or 'x'. This usually leads to misunderstanding. In arithmetic, letters are used as abbreviations for measurements, for example if the length of the garden is known to be 12 m. which means 12 meters. sometimes 3a + 4b which means '3 apples and 4 bananas'. In the context of algebra, 3a + 4b means 3 times a plus 4 times b, that is, a and b do not represent apples and bananas, they stand alone for unknown numbers. If ‘a’ is 5 and ‘b’ is 2 then 3a + 4b will be 3x5 + 4x2 = 15 + 8 = 23.